Terrorism and the Media - Michael Jetter (Institute for the Study of Labor (IZA), 2014)
This paper systematically analyzes media attention devoted to terrorist attacks worldwide between 1998 and 2012. Several aspects are related to predicting media attention. First, suicide missions receive significantly more coverage, which could explain their increased popularity among terrorist groups. This result is further supported by Oaxaca-Blinder decompositions, suggesting that it is not the particular characteristics of suicide attacks (e.g., more casualties) that are driving heightened media attention. Second, less attention is devoted to attacks in countries located further away from the US. Third, acts of terror in countries governed by leftist administrations draw more coverage. However, this finding is not confirmed for suicide attacks conducted in countries ruled by leftist administrations. Fourth, the more a country trades with the US, the more media coverage an attack in that country receives. Finally, media attention of any terror attack is both predictive of the likelihood of another strike in the affected country within seven days' time and of a reduced interval until the next attack.
Keywords: F52; L82; N40; Z12; 330; terrorism; media attention; suicide attacks; political orientation